Efeitos da cocaína e da provação de sono sobre oscilações hipocampo-corticais, sono e memória. - Igor Menezes Gonçalves Rego (2022)
Stimulant drugs such as amphetamine and cocaine act as modulators of the dopaminergic system, being able to induce plastic changes in circuits associated with memory and reward. However, it is still unclear how associative memories of substance use are established in a lasting and persistent way in cortical networks. One possibility is that this occurs, at least partially, during sleep following drug use. We previously demonstrated that single cocaine exposure was able to increase sleep onset latency and subsequently induce a significant increase in delta power (0.5 - 4 Hz) in both the hippocampus and medial prefrontal cortex (mPFC) during slow wave sleep. In this study, we tested whether such observed electrophysiological effects are due to specific cocaine-induced mechanisms or whether they could be mimicked by a sleep deprivation protocol in which deprivation is induced by walking on a treadmill. Adult Wistar rats were chronically implanted with electrodes in the mPFC and CA1 region of the hippocampus to record local field potentials. One week later, the animals were habituated to the recording box and, on the following day, to the recording session (Day 1). On Day 2, the animals received a systemic injection of 0.9% saline, cocaine 15 mg/kg, or underwent treadmill-induced sleep deprivation for 3 hours (4 cm/s) and then recorded. On the third day, the animals were registered again. Concurrently, a second group of animals underwent an object recognition test, with two days of habituation for 20 minutes in the test box (Days -1 and 0), followed by one day of memory encoding (Day 1) for 20 minutes. minutes, after which the mora animals received 0.9% saline injection, 15 mg/kg cocaine or were sleep deprived on a treadmill for 3 hours (4 cm/s). We did not observe significant effects induced by Cocaine 15 mg/kg on memory consolidation in the object location task, while the treadmill-induced sleep deprived group showed worse performance. Both the Treadmill ON and Cocaine 15 mg/kg groups showed an increase in sleep onset latency. During the awake state, we observed an increase in coherence between CA1 and mPFC in the theta frequency band (5 -12 Hz) for both treatment groups compared to saline. After this initial effect, we observed an increase in delta power (1-4 Hz) in both CA1 and mPFC during slow wave sleep subsequent to treatment in both treated groups when compared to the saline group. Despite the diversity of reported effects, all parameters evaluated returned to baseline status 24 h after treatment. In conclusion, our study demonstrated that there is high similarity between the electrophysiological effects induced by cocaine and treadmill-induced sleep deprivation, although their effects on object location memory consolidation differ. Based on our findings, we hypothesized that single exposure to cocaine is capable of activating mechanisms responsible for compensating for memory impairments typically induced by sleep deprivation.